BARRIERS IN ACCESSIBILITY OF DENTAL AND ORAL HEALTH SERVICES FACILITIES DURING THE COVID-19 PANDEMIC AT WEST DENPASAR II PUBLIC HEALTH CENTER - Atsila, Farah Mega; Rejeki, Putri; Dewi, Desak Dhyana Nitha; Giri, Putu Ratna Kusumadewi (Journal of Health and Dental Sciences, 2024)
Accessibility of dental and oral health service facilities is influenced by three indicators, namely availability, barriers and utilization. Barrier indicators cause delays or difficulties for people in accessing these facilities. Barrier indicators are influenced by physical barriers, economic barriers and geographical barriers. Based on preliminary data collection from the Bali Provincial Health Service, West Denpasar II Community Health Center experienced a significant decline in visitors during the COVID-19 pandemic. This research aims to determine the barriers to accessibility of dental and oral health service facilities during the COVID-19 pandemic at the West Denpasar II Health Center and to determine the influence of the COVID-19 pandemic on barriers to accessibility of dental and oral health service facilities at the West Denpasar II Health Center. This research uses quantitative analytical methods with a retrospective approach. The sample for this research was visitors to the West Denpasar II Community Health Center who met the inclusion criteria, totaling 134 respondents. Samples were taken using non-probability sampling techniques with consecutive sampling type. The research results stated that during the COVID-19 pandemic, the accessibility of dental and oral health service facilities at the West Denpasar II Health Center was in the fairly easy access category and obstacles in the accessibility of dental and oral health service facilities at the West Denpasar II Health Center were in the hampered category. Based on the results of correlation tests between barrier factors and accessibility factors for dental and oral health service facilities during the COVID-19 pandemic, it was found that these two factors did not have a significant relationship. The research conclusions show that there were obstacles in the accessibility of dental and oral health service facilities during the COVID-19 pandemic at the West Denpasar II Health Center and there was no influence between the COVID-19 pandemic and obstacles in the accessibility of dental and oral health service facilities at the West Denpasar II Health Center. DOI : 10.54052/jhds.v4n1.p15-24